Evaluation of the Utilization of Web-based Library Application Information Systems using Whitebox and Blackbox Testing Methods - Pamungkas, Ananda Cipta; Samihardjo, Rosalin (Applied Information System and Management (AISM), 2024)
The library information system is a computerized process for integrated data management. This research was conducted in the library located at SMAN 12 Bandung, Jl. Sekejati No. 36, Sukapura. The importance of performance measurement. The validity of implementation from the perspective of effectiveness and efficiency of web-based libraries is the main thing in the aim of managing library digitalization. This research was carried out using the Whitebox and Blackbox Testing integration method. The purpose of the research is to conduct an Information Technology Audit with the validity of measuring the effectiveness and efficiency of application functions. The research results show that the technical analysis of FlowGraph Whitebox is based on source code and flowcharts running on Cyclomatic Complexity which counts the number of nodes and edges in FlowGraph. Research implications support the assessment of the concrete validity of the method used. This can be seen from the research results that the performance of the Web-based Widyantara Library application at SMAN 12 Bandung is considered satisfactory with a good level of validity, this is proven by the test results using the white box testing method. Meanwhile, based on the analysis of the black box testing method on application functionality, the test results are said to be good with a validity percentage reaching 100%. Validity according to application design is proven by testing 10 application scenarios.